Adsorption properties of aqueous methylene blue on mesocellular foam silica: Equilibrium, kinetic, isotherm, and thermodynamic characterization. Issue 5 (3rd September 2019) - Zhai, Qing-Zhou; Dong, Yuan
Abstract: Mesocellular foam silica was prepared by a hydrothermal synthesis protocol. The surface and pore structure of mesocellular foam silica were characterized by low temperature nitrogen adsorption isotherms, X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and Fourier transform infrared (FT-IR) spectroscopy. The methylene blue was adsorbed by the synthetic mesocellular foam silica; the optimized adsorption conditions were evaluated and the maximum adsorption capacity of methylene blue by mesocellular foam silica was determined to be 215.5 mg g −1 . The kinetics of the adsorption of methylene blue by mesocellular foam silica were in accordance with a quasi-second-order kinetic equation. The results were analyzed by Langmuir and Freundlich adsorption isotherm models. The adsorption of methylene blue on mesocellular foam silica was shown to follow the Freundlich adsorption isotherm model. The Gibbs free energy change during adsorption showed that this process was spontaneous. The enthalpy change in the process was –28.868 J·mol −1 K −1, indicating that the adsorption is exothermic. The negative value of entropy –49.296 J·mol −1 K -1 shows that the system disorder decreases due to adsorption.